SAT0223 Predictive factors of early failure to first line treatment with methotrexate in patients with rheumatoid arthritis. results from the gisea registry. (12th June 2018) - Manfredi, A.; ,; Sebastiani, M.; Iannone, F.; Gremese, E.; Bortoluzzi, A.; Favalli, E. G.; Gorla, R.; Salaffi, F.; Fusaro, E.; Foti, R.; Cantarini, L.; et al.
Abstract : Background: Methotrexate (MTX) is generally recommended as first-line treatment of rheumatoid arthritis (RA). Despite its efficacy is well established, a percentage of patients fails the treatment. Few studies investigated the causes of early discontinuation of MTX; a two-year retention rate of about 66% is described for RA patients with lower age and longer disease duration as independent predictors for discontinuation. Objectives: Aim of this study was to detect possible predictive factors for early discontinuation of MTX prescribed as first line treatment in RA patients enrolled in the GISEA (Italian Group for the Study of Early Arthritis) registry. Methods: RA patients who began MTX as first line treatment were included in the study. For all patients age, sex, disease duration, smoking status, the intake of glucocorticoids, clinical and serological data, comorbidities and extra-articular manifestations were collected. Results: We analyzed 612 RA patients (females/males 477/132, mean age 55.73±14.5 years; mean DAS28 5.35±1.5); rheumatoid factor (RF) was positive in 64.9%, anti-citrullinated peptide antibodies (ACPA) in 42.7%. Comorbidities were observed in 17.5% of patients, while extra-articular RA manifestations were recorded in 1.5%; 68.3% of subjects taken low doses of steroids. One hundred and forty-nine (24.3%) patients discontinued MTX during the first year (for inefficacy in 66/149 (44.3%) patients, adverse events in 51/149 (34.2%), and other reasons in 32/149 (21.5). At univariate analysis early discontinuation of MTX was associated to a lower mean age (p=0.041) and a higher mean tender and swollen joints count (p=0.001 and p=0.024, respectively). Age and tender joints count were confirmed at multivariate analysis (OR 1.014, CI95% 1.001–1.027 and OR 0.951, CI95% 0.923–0.981, respectively) as independent predictors of early withdrawal of MTX. Conclusions: More than 75% of RA patients treated with MTX as first-line therapy remained in treatment after 12 months. Age was directly correlated and tender joints count was inversely correlated with early withdrawal of MTX in RA patients. Disclosure of Interest: None declared